Rolf Stein's Tibetica antiqua : with additional materials - Stein, R. A. (Rolf Alfred), 1911-1999.; McKeown, Arthur P. (Leiden ; Boston : Brill, 2010)
Tibetica antiqua represents the seminal work on Tibetan religious history by one of the foremost Tibetologists of the twentieth century. Herein, Stein discusses the cultural and religious interactions among Tibet, India, and China which resulted in what we now consider "Tibetan Buddhism" from the point of view of our earliest sources, the Dunhuang manuscripts. Stein first discusses the basic tool of religious language, and the extent to which translations from Chinese, often apocryphal, scriptures competed with translations from Sanskrit. Stein also analyzes evidence for the introduc.
Tibetica antiqua I. The two vocabularies of Indo-Tibetan and Sino-Tibetan translations in the Dunhuang manuscripts -- Tibetica antiqua II. The use of metaphors for honorific distinctions in the epoch of the Tibetan kings -- Additional note to Tibetica antiqua I -- Tibetica antiqua III. Apropos of the word Gtsug lag and the indigenous religion -- The dating -- Characteristics of the ancient religion -- The sense of Gtsug and gtsug lag -- Review of the sources -- Appendix. The etymology of gtsug lag -- Recapitulation -- Tibetica antiqua IV. The tradition relative to the debut of Buddhism in Tibet -- The religious kings and the royal laws -- The sūtra fallen from the sky -- Recapitulation -- Tibetica antiqua V. The indigenous religion and the Bon po in Dunhuang manuscripts -- Theories -- The ancient religion -- Bon pos and Bon -- Theories on the antecedents of late Bon -- The Dunhuang manuscripts and the later tradition -- Dunhuang documents -- Bon po in the texts translated from Chinese and bon po communities -- Translations from Chinese -- Bon po communities -- Bon po and gshen, their differences and their functions -- Gshen rab mi bo -- Other people -- Names and their epithets -- Themes -- Funerary ritual -- Divinities -- The word Bon alone -- Linguistic and stylistic traits -- Tibetica antiqua VI. Confucian maxims in two Dunhuang manuscripts -- Annuaire 1967 -- Aspects of the sworn faith in China -- The Bonpo cosmogonies in Tibet and near the Mosso -- Annuaire 1968 -- Daoist texts relative to the transmission of revealed books -- The Bonpo accounts on the beginnings of culture -- Annuaire 1969 -- Bonpo accounts on the first men -- Some aspects of the Daoist parishes -- Annuaire 1970 -- Popular cults in organized Daoism -- Elements constitutive of the Bonpo literature -- Bibliography of Rolf A. Stein.
Includes bibliographical references (pages 343-354) and indexes.
Transl. from the French.
Print version record.
Master record variable field(s) change: 650
Keywords: Tibet Autonomous Region (China) -- Civilization; Tibet Autonomous Region (China) -- Civilization -- Sources; Indigenous peoples -- China -- Tibet Autonomous Region -- Religion; Buddhism -- China -- Tibet Autonomous Region -- History; Buddhism -- China -- Tibet Autonomous Region -- History -- Sources; Taoism -- China -- Tibet Autonomous Region -- History; Tibet Autonomous Region (China) -- Religion; Buddhist literature -- China -- Tibet Autonomous Region -- History and criticism; Tibetan language -- Texts; Dunhuang Caves (China) -- Antiquities; Religion; RELIGION -- Buddhism -- History; Antiquities; Buddhism; Buddhist literature; Civilization; Indigenous peoples -- Religion; Religion; Taoism; Tibetan language; China -- Dunhuang Caves; China -- Tibet Autonomous Region; Electronic books; Criticism, interpretation, etc; History; Sources; Texts